Pengaruh Kualitas Pelayanan dan Kualitas Produk terhadap Kepuasan Nasabah pada PT. Bank Tabungan Negara Kantor Cabang Syariah Medan - Mega Lestari; Siti Mujiatun (El-Mal: Jurnal Kajian Ekonomi & Bisnis Islam, 2024)
This study aims to analyze the influence of service quality and product quality on customer satisfaction at PT. Bank Tabungan Negara (BTN) Syariah Branch Office in Medan. Service quality and product quality are considered two key factors that can affect customer satisfaction in the Islamic banking industry. The research method used is quantitative, with data collected through questionnaires distributed to BTN Syariah Medan customers. The collected data were analyzed using multiple linear regression to determine the extent to which these two independent variables influence customer satisfaction as the dependent variable. The results of the study indicate that both service quality and product quality have a positive and significant impact on customer satisfaction. Service quality, which includes aspects such as speed, friendliness, and staff professionalism, is proven to be a primary factor in enhancing customer satisfaction. Additionally, product quality, which encompasses various offered Islamic banking products, also has a significant contribution to customer satisfaction. The conclusion of this study is that PT. Bank Tabungan Negara Syariah Branch Office in Medan needs to continuously improve their service quality and product quality to achieve higher customer satisfaction levels. The practical implications of this study show that improvements in these two aspects can increase customer loyalty and drive the growth of the Islamic banking business. This research provides an important contribution to the Islamic banking literature and offers strategic recommendations for bank management in their efforts to enhance the quality of their services and products.